(untitled) (Studia theodisca, 2020)
In this essay I revisit a vexed question, namely how to translate the term “Geschik” in Hölderlin’s theoretical writings. There are two places where its interpretation is contentious: in a passage from the Anmerkungen zur Antigonä, and in the first letter to Böhlendorff. In his writings he frequently uses the term to mean “fate”, but this is not an invariable rule. Depending upon the context, other interpretations (for instance “skill”) cannot always be excluded. It is also clear that Hölderlin enjoys playing on the etymological and phonetic relations between this and cognate expressions.